Economic evaluation and decision-making in health. The role of economic evaluation in the adoption and spread of health technologies. 2008 SESPAS report - Oliva, J; Antoñanzas, F; Rivero-Arias, O (2008)
Economic evaluation of health care technologies (EEHT) has become a basic tool in the decision-making process in health. The continuous development of methods and their direct application to reality have placed EEHT as a key item on the agenda of health policy makers across countries. The present article introduces the aims of EEHT and describes the experience of several European countries where economic evaluation studies are currently used to select the health technologies to be implemented. The role played by EEHT in Spain at the present time is then discussed. Finally, pressing tasks are identified and recommendations are made for the consolidation of EEHT as a basic element in the decision-making process of health care technologies.